Role of liquid biopsy for thoracic cancers immunotherapy - Raimondo Di Liello; Flora Cimmino; Soraya Simón; Emilio Francesco Giunta; Vincenzo De Falco; Paloma Martín-Martorell (Open Exploration Publishing Inc., 2020)
Immunotherapy has shifted the therapeutic landscape in thoracic cancers. However, assessment of biomarkers for patient selection and disease monitoring remain challenging, especially considering the lack of tissue sample availability for clinical and research purposes. In this scenario, liquid biopsy (LB), defined as the study and characterization of biomarkers in body fluids, represents a useful alternative strategy. In other malignancies such as colorectal cancer, breast cancer or melanoma, the potential of LB has been more extensively explored for monitoring minimal residual disease or response to treatment, and to investigate mechanisms of resistance to targeted agents. Even if various experiences have already been published about the applications of LB in immunotherapy in thoracic cancers, the standardization of methodology and assessment of its clinical utility is still pending. In this review, the authors will focus on the applications of LB in immunotherapy in non-small cell lung cancer, small cell lung cancer, and malignant pleural mesothelioma, describing available data and future perspectives.